Optimization of the Roles of Mosques and Religious School in Cikawungading Village, Cipatujah District (Real Work Lecture Program Group 5, 4th Generation, STIABI Riyadul ‘Ulum) - Rahmat Mulya Nugraha; Ade Adin Sahrudin; Farel Luthfi Firdaus; Isep Pahmi Aolia; Muhammad Dzickry Azharul Jinan Al Faridz; Hilman Maulana Yusuf; faisal; Muhammad Izza Anil Mu'ir (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Community service is one form of implementing knowledge and technology to directly benefit society. This study aims to describe the role of the community service program (KKN) group 5 in implementing the KKN program in the cikawungading area, cipatujah district, with a focus on optimizing the role of mosques and religious schools in community development. The research methods used are observation, interviews, and documentation. The results show that through the KKN program, group 5 was able to actively contribute to enhancing the role of mosques and religious schools as educational centers and social activity centers in the community. Activities included religious counseling, character building, waste management, as well as skills development and creative economic activities. Thus, community service through KKN can be an effective means of building local potential and enhancing the holistic well-being of the community.